Cryoablation and immunity in non-small cell lung cancer: a new era of cryo-immunotherapy - Velez, Antonio; DeMaio, Andrew; Sterman, Daniel (Frontiers in Immunology, 2023)
Despite remarkable advances in tumor response and patient survival in the past decade, systemic immunotherapies for lung cancer result in an objective response in only around half of patients treated. On the basis of this limitation, combination strategies are being investigated to improve response rates. Cryoablation has been proposed as one such technique to induce immunogenic cell death and synergize with systemic immunotherapies, including immune checkpoint inhibitors. Cryoablation has been traditionally delivered percutaneously with imaging guidance although recent technological advances allow for bronchoscopic delivery. Herein, we review the pre-clinical and clinical evidence for the use of cryoablation in non-small cell lung cancer and potential induction of anti-tumor immunity. We highlight ongoing studies involving this approach and propose areas of future investigation.